Broadband tapered planar monopole antenna with parasitic elements for multiple wireless operations. Issue 3 (5th February 2018) - Karakus, C.; Dogusgen (Erbas), C.; Yurt, S. C.; Kent, S.
Abstract: We designed a planar monopole antenna with an impedance matching part and two rectangular parasitic elements. Parasitic elements significantly increased radiation bandwidth and gain. Measured fractional bandwidth and maximum gain for the case with parasitic elements were 129.9% and 5.67 dB, respectively. Antenna operated between 675 MHz and 3177.5 MHz.